The Nordic concept of 'faellesskab'. Issue 1 (March 1991) - Riis, P
Abstract : The complex of cultural, political and societal affiliations, both in a historic and a contemporary perspective, is expressed by a special term in the Nordic languages, 'faellesskab', often with the addition of 'folkelig', as 'folkeligt faellesskab', where 'folkelig' means of the people. No corresponding term exists in English. For medical ethics the concept 'faellesskab', or whatever wording is chosen to serve the semantics of this term, is vital. In research ethics and clinical decision-making complex ethical analyses and normative evaluations are necessary. They cannot be based solely on moral relativism, whether being based on results of opinion polls or on a widespread 'every man minds his own business' concept. 'Faellesskab' possesses the necessary base of common values.